Using Linked Data to Explore the Relationship Between Walking-Friendliness of Neighbourhoods, Physical Activity and Body Mass. (2017) - Ross, Nancy; Dasgupta, Kaberi; Sanmartin, Claudia; Wasfi, Rania; Hajna, Samantha; Mah, Sarah
No abstract available